(untitled) (Global Journal of Science Frontier Research, 2016)
Cross-sectional study for determining the prevalence of Ovine pasturellosis, in-vivo evaluation of the level of protective antibody titer before and after vaccination against the disease and proofing the farmers and animal health experts complaint of its cause on small ruminant production despite annual vaccination program against the disease in Adiyo district of Boka-Shuta and Buta Kebelle, Kaffa Zone. The study was conducted from July 2012 to June 2013 and the study kebelles were purposively selected based on sheep production potential, the disease’s report and farmers’ complaint on the vaccine’s inefficacy for protecting the sheep against the disease. For these, the study was designed to answer the above stated objectives with two consecutive phases, viz. prevalence study followed by in-vivo antibody titer evaluation. For prevalence study, 192 blood samples were needed and calculated, but for more accuracy 200 samples were collected randomly from previously unvaccinated sheep population (in less than 1 year) against ovine pasturellosis disease.